Policy and legal perspectives on the traditional Chinese medicine varietal protection system (TCMVPS): reform or abolition? - Wang, Yanhui; Sun, Ke; Hua, Dong (Frontiers in Pharmacology, 2026)
BackgroundThe Traditional Chinese Medicine Varietal Protection System (TCMVPS) was introduced in 1993 as a regulatory mechanism intended to safeguard key formulations, ensure product quality, and provide incentives for industrial development. After more than three decades of implementation, the system has played a role in stabilizing the market and preserving certain classic varieties. At the same time, its effectiveness and long-term relevance have become a matter of debate.MethodsThis study reviews the legislative framework, implementation history, and current practice of the TCMVPS. It draws on policy documents, regulatory guidelines, and existing scholarship to examine how the system interacts with related regimes such as patents and drug registration. A comparative perspective is also adopted to highlight distinctive features and limitations. This study provides the comprehensive empirical and policy analysis of the TCMVPS’s evolution and reform prospects, contributing to the broader debate on sui generis protection of traditional medical knowledge.ResultsThe analysis shows that the system has contributed to protecting well-known TCM products and provided a degree of market exclusivity for approved varieties. However, several weaknesses have emerged: the narrow scope of protection, the ambiguous relationship with intellectual property law, the quasi-mandatory nature of applications under market pressure, and the reduced incentive for continuous innovation during the protection period. These challenges have limited the system’s capacity to balance protection with innovation and competition.ConclusionThe TCMVPS illustrates the opportunities and pitfalls of designing sui generis mechanisms for traditional medicine protection. Its future relevance depends on substantive reform, including clearer alignment with intellectual property and drug regulatory frameworks, expansion of eligible categories, and the incorporation of mechanisms that encourage continuous clinical and technological improvement. Beyond China, the experience of the TCMVPS provides valuable lessons for other jurisdictions seeking to reconcile traditional knowledge preservation with modern regulatory and innovation systems.